2009
DOI: 10.1007/s00267-009-9355-z
|View full text |Cite
|
Sign up to set email alerts
|

Land-Use and Land-Cover Dynamics in the Central Rift Valley of Ethiopia

Abstract: Understanding the complexity of land-use and land-cover (LULC) changes and their driving forces and impacts on human and environmental security is important for the planning of natural resource management and associated decision making. This study combines and compares participatory field point sampling (pfps) and remote sensing to explore local LULC dynamics. The study was conducted in two peasant associations located in the central Ethiopian Rift Valley, which is a dry-land mixed farming area exposed to rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 38 publications
7
123
0
Order By: Relevance
“…The cross-tabulation matrices show that the most prominent transition from 1972 to 2010 is a conversion from woodland to cropland, which accounts for 51.96 % of the landscape. Different studies also showed an increase in area of cropland in other parts of the country [Reid et al, 2000;Garedew et al 2009;Lemenih et al, 2012;Kindu et al, 2013] and globally [Lambin et al, 2003;Hanafi and Jauffret, 2008]. The rapid vegetation removal has exposed the topsoil to wind and water erosion processes.…”
Section: Dynamics Of Lulc Transition Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-tabulation matrices show that the most prominent transition from 1972 to 2010 is a conversion from woodland to cropland, which accounts for 51.96 % of the landscape. Different studies also showed an increase in area of cropland in other parts of the country [Reid et al, 2000;Garedew et al 2009;Lemenih et al, 2012;Kindu et al, 2013] and globally [Lambin et al, 2003;Hanafi and Jauffret, 2008]. The rapid vegetation removal has exposed the topsoil to wind and water erosion processes.…”
Section: Dynamics Of Lulc Transition Matrixmentioning
confidence: 99%
“…During the study period, major land use classes have shown a significant transition like most parts of the country [Reid et al, 2000;Garedew et al, 2009;Tsegaye et al, 2010] and other dry land areas [Lambin et al, 2003;Hanafi and Jauffret, 2008]. The land cover transition is higher for woodland, cropland and grassland within the landscape.…”
Section: Persistence Of Land Usesmentioning
confidence: 99%
“…The Rift Valley area is one of the regions that suffer most from rapid deforestation that has led to the decrease in the biodiversity of the woodlands for intensive agriculture and settlement for the ever increasing small-hold farming community (Garedew et al, 2009). It is also established that agricultural development can change the whole spectrum of AMF associations that are specifically associated with fitness of specific plants, plant community structure and ecological variability (Van der Heijden et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the pressure are manifold: intensified agriculture, decreasing amount of forest land, loss of biodiversity, intensified land degradation and soil erosion [10]. Deforestation rates in East Africa, including Ethiopia, were the second highest in Africa: 0.94% for 1990-2000 and 0.97% for 2000-2005 [11]. A study conducted in North Western Ethiopia indicated 99% clearing of the forest cover of the 1950s until the year 1995 [12].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in North Western Ethiopia indicated 99% clearing of the forest cover of the 1950s until the year 1995 [12]. The population of Ethiopia, which is currently 79 million people, increases by almost two million annually under highly unfavorable economic and environmental conditions [11]. Population pressures in Ethiopia have decreased the size of holdings, including both arable and pasture lands, leading to conversion of forested and marginal areas into agricultural lands [13].…”
Section: Introductionmentioning
confidence: 99%